Insulating Material Erosion in Atmospheric Non-Thermal Plasma Jet Device - Kamal M Ahmed; Tarek M Allam; Mohamed Anwar Abouelatta; Sayed A Ward; Ahmed A Lashin; Hanaa M Soliman (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper reports on the selection of insulating material types in a developed atmospheric-pressure non-thermal plasma jet (ANPJ-II) device which was operated previously in our laboratory based on the minimum erosion area of the insulator’s nozzle. Three identical insulator groups used in our experiment include; Teflon insulator material with different thicknesses of 1.5 mm and 2 mm respectively, and Ceramic insulating material with thickness of 2 mm. ANPJ-II device is operated with each of the three insulator groups. These insulators are operated and analyzed with different operation times for compressed Air or Nitrogen gas with a flow rate of 12 L/min and input voltage of 6 kV.  The erosion area of these insulator materials is measured as a function of the operation time. The Ceramic insulator was found to have the minimum erosion area. Also, the temperature of both the cathode and the insulating material (Teflon or Ceramic) are measured to study the effect of operation time and the gas type on the device components.